Risk-based maintenance planning of subsea pipelines through fatigue crack growth monitoring. (September 2017) - Arzaghi, Ehsan; Abaei, Mohammad Mahdi; Abbassi, Rouzbeh; Garaniya, Vikram; Chin, Christopher; Khan, Faisal
Abstract: Research and development in the field of risk-based maintenance of offshore structures has recently attracted large attention due to the significant level of accident risk and the cost associated with maintenance in such remote facilities. The uncertainties associated with the deterioration of these facilities require a sound decision making methodology for maintenance planning. This paper presents a dynamic risk-based methodology for maintenance scheduling of subsea pipelines subjected to fatigue cracks. The developed method can assist the asset managers to select the optimum approach for mitigating the consequences of failure while minimizing the maintenance costs. A Bayesian network is developed to model the probabilistic deterioration process and then it is extended to an influence diagram for estimating the expected utility of each decision alternative. Observation of damage state is included in the model to enhance decision making capacity. To demonstrate the applicability of the methodology, three cases with different fatigue crack incidents on a pipeline are considered. Based on the monitoring results, the model is able to determine whether the maintenance should be performed or not. The economic risk associated with maintenance is also minimized by suggesting the optimum maintenance technique among multiple possible methods such as welding or major repair. Highlights: Application of Bayesian network (BN) and influence diagram (ID) to multi-criteria decision making (MCDM) Development of a novel methodology for maintenance planning in offshore oil and gas applications Integration of a probabilistic model and multi-attribute decision making for risk-based maintenance of offshore pipelines Minimization of the economic risk of maintenance and selection of the repair task with optimum outcome